Understanding Parkinson’s Pathology is Key to Early Detection and Treatment - Nichols, Emma Hitt (MD Conference Express, 2014)
Understanding the underlying pathology of Parkinson’s disease (PD) is critical in identifying the disease early and developing novel treatments. This article discusses the role of a-synuclein in PD, the extranigral pathology and preclinical detection of PD, as well as how the updated understanding of PD pathology explains its clinical phenotype